2015
DOI: 10.1089/aid.2014.0159
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation Challenges of a Quality Assured HIV Infant Diagnosis Program in Nigeria Using Dried Blood Spots and DNA Polymerase Chain Reaction

Abstract: Nigeria has one of the highest HIV burdens as well as mother-to-infant transmission rates in the world. A pilot program using polymerase chain reaction (PCR)-based testing of dried blood spot (DBS) specimens was implemented to enable early identification of HIV-infected infants and timely referral and linkage to care. From February 2007 to October 2008, whole blood was collected by finger prick to prepare DBS from infants < 18 months presenting in six public mother-and-child health facilities in Lagos, Nigeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Fifteen studies involving 5863 participants reported on the MTCT rate of HIV in mother–infant pair with HIV mono-infection when all the pregnant women living with HIV received triple antiretroviral therapy, as treatment or prophylaxis, regardless of breastfeeding habit. 20 – 34 The MTCT rates for HIV were reported to be 0.0% by Eleje et al, 20 Okafor et al, 21 and Ben and Yusuf, 22 0.4% by Sagay et al, 23 1.0% by Onubogu et al, 24 1.3% by Chukwuemeka et al, 25 1.7% by Kalu et al, 26 2.18% by Isah et al, 27 2.8% by Ikechebelu et al, 28 3.4% by Oluwayemi, 29 4.0% by Markson and Umoh, 30 4.5% by Afolabi et al, 31 4.8% by Anoje et al, 32 5.4% by Itiola et al, 33 and 9.6% by Afe et al 34 at 6 weeks to 18 months following PCR analysis. The results of our meta-analysis revealed that the pooled MTCT rates for HIV mono-infections as seen in the 15 included studies that reported on HIV mono-infections was 2.74% (95% CI: 2.48%–2.99%; 5863 participants; 15 studies; I 2 = 100%; p-value < 0.001) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies involving 5863 participants reported on the MTCT rate of HIV in mother–infant pair with HIV mono-infection when all the pregnant women living with HIV received triple antiretroviral therapy, as treatment or prophylaxis, regardless of breastfeeding habit. 20 – 34 The MTCT rates for HIV were reported to be 0.0% by Eleje et al, 20 Okafor et al, 21 and Ben and Yusuf, 22 0.4% by Sagay et al, 23 1.0% by Onubogu et al, 24 1.3% by Chukwuemeka et al, 25 1.7% by Kalu et al, 26 2.18% by Isah et al, 27 2.8% by Ikechebelu et al, 28 3.4% by Oluwayemi, 29 4.0% by Markson and Umoh, 30 4.5% by Afolabi et al, 31 4.8% by Anoje et al, 32 5.4% by Itiola et al, 33 and 9.6% by Afe et al 34 at 6 weeks to 18 months following PCR analysis. The results of our meta-analysis revealed that the pooled MTCT rates for HIV mono-infections as seen in the 15 included studies that reported on HIV mono-infections was 2.74% (95% CI: 2.48%–2.99%; 5863 participants; 15 studies; I 2 = 100%; p-value < 0.001) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the ongoing study, we excluded six articles that we retrieved; as they did not meet the inclusion criteria 6,[15][16][17][18][19] (see Table 2). Table 3 presents the main characteristics of the 18 included studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The MTCT rate of 22.0% and 22.5% from studies conducted by Afe et al, (2011) and Audu et al (2014) using data gathered between February 2007 and October 2008 at six health facilities (each) in Lagos State, Nigeria fell within our confidence intervals for 2008 (14.3% (95%CI 4.4% - 24.2%)) [19,20]. Our overall MTCT rate estimate of 11.25%, using pooled data from 2008–2012 was very close to the MTCT rate of 11.0% at 17 weeks, found in four secondary health facilities in Kwara and Niger States, Nigeria, 2009–2012 [30].…”
Section: Discussionmentioning
confidence: 50%
“…22 As would be expected, children with perinatally acquired HIV infection in Africa are older at the time of diagnosis than are infected children born in the United States. 23 Given the high loss to follow-up of HIV-exposed infants in SSA 24 , we should consider the possibility that HIV-exposed infants born elsewhere who move here at very young ages might not yet have undergone sufficient diagnostic testing to rule out HIV infection. In the present study, HIV in foreign-born children was diagnosed at older ages than in US-born.…”
Section: Discussionmentioning
confidence: 99%